2015
DOI: 10.1007/s00592-015-0727-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of and risk factors for hypoglycemia and associated arrhythmias in patients with type 2 diabetes and cardiovascular disease: a cohort study under real-world conditions

Abstract: In conclusion, our study suggests that hypoglycemia might be able to trigger at least under certain circumstances, such as low TSH, ventricular arrhythmias under real-world conditions. The large number of unrecognized HE and VT in vulnerable patients treated with insulin or sulfonylurea should encourage the practitioner to focus on stable glucose control and to search for silent HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 17 publications
0
50
0
1
Order By: Relevance
“…Hypoglycaemia-induced heart rhythm disorders are particularly dangerous in patients with cardiovascular diseases in whom catecholamine hypersecretion may increase oxygen requirement and the exacerbation of ischaemia. Ventricular arrhythmias in patients with type 2 diabetes and cardiovascular disease may be above 30 times more frequent than in patients without hypoglycaemia [22]. It is extremely important that in the cited study only 39% of patients noted hypoglycaemic symptoms during the day, and even fewer -11% -reported nocturnal hypoglycaemia.…”
Section: Cardiac Arrhythmiasmentioning
confidence: 94%
See 2 more Smart Citations
“…Hypoglycaemia-induced heart rhythm disorders are particularly dangerous in patients with cardiovascular diseases in whom catecholamine hypersecretion may increase oxygen requirement and the exacerbation of ischaemia. Ventricular arrhythmias in patients with type 2 diabetes and cardiovascular disease may be above 30 times more frequent than in patients without hypoglycaemia [22]. It is extremely important that in the cited study only 39% of patients noted hypoglycaemic symptoms during the day, and even fewer -11% -reported nocturnal hypoglycaemia.…”
Section: Cardiac Arrhythmiasmentioning
confidence: 94%
“…Disorders including QT prolongation and ventricular arrhythmias related to hypoglycaemia were also reported in patients with type 2 diabetes [21,22]. This problem affects not only patients treated with insulin but also those receiving sulfonylureas [22,23].…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent metaanalyses published by Huxley et al [3] revealed that patients with DM had a 40% greater risk of developing AF compared to patients without. On the other hand, there has been growing evidence about the relationship between hypoglycaemic episodes and ventricular rhythm disorders for the recent years [4,5] . The relationship between DM and arrhythmic disorders is not fully understood yet and there is a growing population of DM patients everyday.…”
Section: Minireviewsmentioning
confidence: 99%
“…There were high incidence of hypoglycemia and silent VA in the insulin and/ or SU group comparing to control subjects. A study from Pistrosch et al [5] further analyzed effects of hypoglycemia as a trigger for VA in larger patient cohort with type 2 DM revealed that hypoglycemia might be able to trigger VA and interestingly a tiroid stimulating hormone level in the low normal range, which indicates subclinical hypertiroidism, is indepently associated with occurrence of VA. Although these two studies provide no causal relationship between hypoglycemia and VA in diabetic patients, it may be postulated that hypoglycemia may be triggering VA either with sympathetic overstimulation or QT prolongation [36] .…”
Section: Diabetes and Ventricular Arrhythmiasmentioning
confidence: 99%